2000
DOI: 10.1094/cchem.2000.77.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Study of Internal Structure of Waxy Wheat Starch Granules by KI/I2 Solution

Abstract: Wheat starch granules were separated from waxy wheat flour by the acetic acid (pH 3.5) fractionation technique. Waxy wheat starch samples were stained red‐brown using KI/I2 solution. Subsequently, the concentration of the KI/I2 solution was increased to >2.5% KI and 1.0% I2. Then the appearance of the waxy wheat starch granules quickly became ghostlike. The internal structure of the ghost could be observed. This structure consisted of two parts with different colors: a red‐brown central part and a slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…1-3). It was reported by Seguchi et al [1] that waxy wheat starch granules (A-type) showed a remarkable double structure of black-brown central and red-brown surrounding portions, however, this was not observed in B-type waxy wheat starch granules. Twelve kinds of B-type starch granules containing various amounts (2.1,25.0%) of amylose were treated with concentrated KI/I 2 solution, and the relative ghost areas were measured (Tab.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…1-3). It was reported by Seguchi et al [1] that waxy wheat starch granules (A-type) showed a remarkable double structure of black-brown central and red-brown surrounding portions, however, this was not observed in B-type waxy wheat starch granules. Twelve kinds of B-type starch granules containing various amounts (2.1,25.0%) of amylose were treated with concentrated KI/I 2 solution, and the relative ghost areas were measured (Tab.…”
Section: Resultsmentioning
confidence: 77%
“…The concentrated KI/I 2 solution was prepared as follows; KI (25 g) was dissolved in 10% I 2 solution and finally filled up to 100 mL with the same solution. Microphotographs of the B-type starch ghosts were taken as described by Seguchi et al [1].…”
Section: Ghost Of B-type Wheat Starch Granule By Concentrated Ki/i 2 mentioning
confidence: 99%
See 2 more Smart Citations
“…Moisture content was calculated as weight loss after drying at 135 °C for 1 h. Starch granules were stained with 10% iodine-25% potassium iodide solution and microscopically observed as reported [9].…”
Section: Starch and Its Propertiesmentioning
confidence: 99%